(untitled) (Revista de Medicina Clinica, 2022)
Introduction: Cerebral vascular disease (CVD) is a time-dependent neurological emergency in which every minute counts for the functional outcome, so care times must be optimized from the onset of symptoms to arterial recanalization to limit brain damage. Patients and methods: retrospective, cross-sectional, descriptive and observational study, carried out in the “ResISSSTE cerebro” stroke network from March 2021 to February 2022, in patients with suspected acute ischemic stroke of up to 24 hours of evolution. We included 114 patients. The "hub-and-spoke" model was used, in which seven essential centers transferred patients to the advanced center. Results: the time of arrival of the EMS to the essential center was longer for Hospital 1ro de Octubre with 231±14 min and the shortest for H. Darío Fernández with 60±19 min; the average transfer time from essential centers to the advanced center was shorter for H. Darío Fernández with 25±32 min, and the longest corresponded to H. Pachuca with 164±53 min. Conclusion: In the "hub-and-spoke" model, it is essential to optimize the transfer times of patients with cerebral infarction from the essential centers to the advanced center. We found that the transfer times to the advanced center occur optimally, with delays due to the non-availability of the EMS in essential centers. Derived from this analysis, we suggest reorganizing the EMS to ensure availability in essential centers with a greater flow of patients.